Upaya Mengukur Daya Saing Wilayah melalui Indeks Pembangunan Daerah Kabupaten/Kota di Provinsi Sumatera Selatan - Kemas Ahmad Affandi (Universitas Batanghari Jambi, 2020)
This study aims to analyze the performance of regional development in all districts/cities in South Sumatera through the measurement of regional development index as an effort to measure the level of regional competitiveness by examining several indicators that are considered influential. This paper uses quantitative analysis method by measuring the composite index. The main steps in compiling the composite index include standardization, weighting, and aggregation. As a result, the Regional Development Index in South Sumatera Province is unevenly distributed, region with high category index is only Palembang City, while 16 other districts / cities are in the low and medium categories. Issues that must be addressed in almost all districts / cities are the access to clean water, roads, economic growth, poverty level reduction, regional income and accountability of government agencies performance.